ANALISIS KESEJAHTERAAN PEDAGANG KAKI LIMA DI KOTA SIGLI KABUPATEN PIDIE - Rizki Saputra; Eddy Gunawan (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
AbstractThe purpose of this study was to determine the level of welfare of street vendors in Sigli City before with after market relocation. The population in this study were all street vendors, totaling 166 street vendors. Sampling is done using the